Telemedicine as a tool for the digitization of healthcare - D.O. Dziuba; O.V. Khavryuchenko; O.E. Domoratskyi; S.R. Maruniak; A.P. Mazur; O.V. Sharikadze; D.V. Viter (Медицина неотложных состояний, 2025)
Background. The growing demand for healthcare services highlights the importance of improving accessibility, particularly in rural and remote areas. Insufficient integration of technology in public administration calls for implementing telemedicine as a solution to enhance access to healthcare services. The purpose of the study is to determine the prospects for the development of digitization of public administration in the healthcare sector based on the implementation of telemedicine technologies. Materials and methods. The study utilized analytical reviews of scientific publications, statistical data from the Ministry of Health of Ukraine, and comparisons of international experiences in telemedicine implementation. Results. It was found that existing barriers, such as inadequate funding, legislative constraints, and data security issues, hinder the development of telemedicine. However, the application of telemedicine technologies can improve access to medical services, reduce costs, and enhance healthcare quality. Conclusions. Successful implementation of telemedicine in Ukraine requires the development of a clear regulatory framework, investment in infrastructure, and training of medical personnel. Collaboration with the private sector and international organizations is also crucial for ensuring accessibility and quality of healthcare services.